The Descriptive Study on Question Words in Amanatun Dialect of Meto Language - Anselmus Sahan; Darni Nopi Nokas (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2017)
This research is a descriptive study on linguistics which focuses on the question words in Amanatun dialect of Meto language. The purposes of this research are to identify the kinds of question words and to describe how those question words are constructed.The descriptive qualitative method was used in this research. The native speakers of Amanatun dialect as the subject of the research. The instrument used was translation sentences of question words from Indonesia into Amanatun dialect. There were five techniques of data analysis: translation, codification,classification, syntactical analyses, and discussion.The findings show that there are seven kinds of question words in Amanatun dialect. They are sa(what), sekau(who), etme/esme/mbime/neome(where), leka(when), nansa/neusa(why), onme(how) and fauk (how many and how much). Saisplaced at the initial position of the sentence. Sekau is placed in three positions; in initial part of the sentence, in the middle of the sentence and at the final part of the sentence. The question of etme/esme/mbime/neome is placed at the final part of the sentence. Leka is placed in two positions: in the initial part of the sentence and at the final part of the sentence. The question of nansa is placed at the final part of the sentence. Nansa cannot be placed at the final position of the sentence. While neosa is only placed at the final position of the sentence and it cannot be placed in initial position of the sentence. There are three positions of onme; in the initial of the sentence, in the middle of the sentence and the final of the sentence. Fauk is placed at the final part of the sentence.Keywords: question words, Amanatun, Meto